2011
DOI: 10.1042/bj20101685
|View full text |Cite
|
Sign up to set email alerts
|

The expression of nicotinamideN-methyltransferase increases ATP synthesis and protects SH-SY5Y neuroblastoma cells against the toxicity of Complex I inhibitors

Abstract: NNMT (nicotinamide N-methyltransferase, E.C. 2.1.1.1) catalyses the N-methylation of nicotinamide to 1-methylnicotinamide. NNMT expression is significantly elevated in a number of cancers, and we have previously demonstrated that NNMT expression is significantly increased in the brains of patients who have died of Parkinson's disease. To investigate the cellular effects of NNMT overexpression, we overexpressed NNMT in the SH-SY5Y cell line, a tumour-derived human dopaminergic neuroblastoma cell line with no en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
124
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(143 citation statements)
references
References 39 publications
16
124
0
Order By: Relevance
“…Further study showed that when NNMT-overexpressing and control PANC-1 cells were incubated with 2-DG in the presence of rotenone, a mitochondrial inhibitor, there was no significant difference in cell survival between the NNMT-overexpressing and control cells. These results suggested that the increased survival of NNMT-overexpressing PANC-1 cells undergoing glycolysis inhibition may be due to the increased dependence upon oxidative phosphorylation, which was in accordance with previous findings in human neuroblastoma cells [23]. The results indicated NNMT is a gene that involves in the process of cancer metabolic transformation, which may play a critical role in pancreatic cancer progression.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Further study showed that when NNMT-overexpressing and control PANC-1 cells were incubated with 2-DG in the presence of rotenone, a mitochondrial inhibitor, there was no significant difference in cell survival between the NNMT-overexpressing and control cells. These results suggested that the increased survival of NNMT-overexpressing PANC-1 cells undergoing glycolysis inhibition may be due to the increased dependence upon oxidative phosphorylation, which was in accordance with previous findings in human neuroblastoma cells [23]. The results indicated NNMT is a gene that involves in the process of cancer metabolic transformation, which may play a critical role in pancreatic cancer progression.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, a recent study showed that NNMT overexpression was associated with increased radioresistance via regulating nicotinamide metabolism [22]. And Parsons et.al have found that NNMT expression reduced cell death by increasing ATP synthesis and complex I activity [23], and was able to induce changes in cell morphology via ephrin-B2 and Akt signaling in human neuroblastoma cells [24]. And very recently, a study found NNMT depletion induced cell apoptosis via mitochondria-mediated pathway in human breast cancer cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotinamide, a form of vitamin B3, is the precursor of NAD + (a coenzyme that provides oxidoreductive power for the generation of ATP by mitochondria) synthesis and plays a crucial role in cell survival and longevity [3]. Although N-methylation, an important conjugation reaction in the biotransformation of many xenobiotics and drugs, is usually thought to decrease the toxicity of the parent compounds, there are instances in which the converse may occur.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have shown that NNMT overexpression affects cellular damage resistance by depleting accessible amounts of nicotinamide [4], correlates positively with cancer cell migration and tumour stage [5], and is also associated with differentiation and poor prognosis [6,7]. Furthermore, other recent studies have shown that the knockdown of NNMT is able to inhibit the proliferation of KB cancer cells [8], renal carcinoma cells [9], and oral cancer cells [6], and that NNMT expression is involved in the maintenance of cell proliferation by increasing the activity of Complex I (NADH:ubiquinone oxidoreductase) in SH-SY5Y neuroblastoma cells [3]. These results suggest that NNMT supports tumorigenesis and may thus serve as a potential anticancer target.…”
Section: Introductionmentioning
confidence: 99%
“…These effects were replicated by incubation of cells with 1-methylnicotinamide. In the context of pathogenesis of Parkinson's disease, it is important that both NNMT expression and 1-methylnicotinamide protected SH-SY5Y cells from the toxicity of the Complex I inhibitors MPP + and rotenone by reversing their effects upon ATP synthesis, ATP:ADP ratio, Complex I activity and the NDUFS3 subunit (Parsons et al, 2011). Overexpression of SIRT1 or its activation in neuronal and glial cells with resveratrol has been shown to protect the brain tissue from degeneration in Alzheimer's disease and Huntington's disease, and calorie restriction able to modulate SIRT activity is neuroprotective against Parkinson's disease and Alzheimer's disease (Outeiro et al, 2008).…”
Section: Modulation Of Nad + Metabolism In Glial Cells As Therapeuticmentioning
confidence: 99%